(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background and Aim: Hip fractures show quite rarely as traumatic pathology in children. This study aims to enroll the health outcomes of children with hip fractures, as well as assess the quality of life at children during follow-ups at various hospitals of Baghdad, Iraq. Patients and Methods: The cross-sectional study was conducted from January 2024 to January 2025 for reviewing medical records of children aged 2-18 years having a hip fracture and who underwent to Open Reduction and Internal Fixation (ORIF) in different hospitals at Baghdad, Iraq. Total patient inclusion criteria were met by 80 patients whose demographic data, injury mechanisms, treatment modalities, and quality of life, as determined through the SF-36 questionnaire, were evaluated. Results: A data set was collected from 80 children with hip fractures, ranging in age from 2 to 18 years. Transphyseal fracture is being the most prevalent type among the patients, including 42.5% of total patients. Sports-related injuries were identified as the primary cause of fractures in 43.75% of cases. Postoperative complications following open reduction and internal fixation treatment were observed in 20% of cases, with osteonecrosis identified as the most prevalent complication (n = 6). Patient satisfaction levels were recorded as 70%. Conclusion: Our study shows that the open reduction and internal fixation procedure is shown to be a crucial and effective intervention in improving the health and quality of life in children with hip fractures, as well as reducing complications in the long term.